2004
DOI: 10.1080/03009740310004775
|View full text |Cite
|
Sign up to set email alerts
|

Receptor of advanced glycation end product (RAGE) expression in the minor salivary glands of patients with Sjo˝gren's syndrome: a preliminary study

Abstract: RAGE is present in the labial salivary glands of both normal and SS patients, with preliminary data suggesting over-expression in SS tissues. The role of RAGE in the pathogenesis of SS has yet to be determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
25
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 16 publications
0
25
0
Order By: Relevance
“…Egr-1 is developmentally regulated and binds the GC-rich sequence GCG(G/T)GGGCG, which often overlaps the DNA-binding sequence of stimulating protein 1. Competition between stimulating protein 1 and Egr-1 leads to either activation or suppression of common target genes (15,21). Egr-1 is a crucial regulator of cell proliferation, differentiation, and survival after induction by several stimuli such as growth factors, cytokines, radiation, apoptosis-promoting factors, injury, and stretch (4,15,27).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Egr-1 is developmentally regulated and binds the GC-rich sequence GCG(G/T)GGGCG, which often overlaps the DNA-binding sequence of stimulating protein 1. Competition between stimulating protein 1 and Egr-1 leads to either activation or suppression of common target genes (15,21). Egr-1 is a crucial regulator of cell proliferation, differentiation, and survival after induction by several stimuli such as growth factors, cytokines, radiation, apoptosis-promoting factors, injury, and stretch (4,15,27).…”
mentioning
confidence: 99%
“…Competition between stimulating protein 1 and Egr-1 leads to either activation or suppression of common target genes (15,21). Egr-1 is a crucial regulator of cell proliferation, differentiation, and survival after induction by several stimuli such as growth factors, cytokines, radiation, apoptosis-promoting factors, injury, and stretch (4,15,27). Furthermore, depending on the stimulus and cell type, various signal transduction pathways induce Egr-1, including those mediated by the mitogen-activated protein kinases extracellular signal-regulated kinase 1/2, protein kinase C-␤, Rho GTPase, or p38/c-Jun NH 2 -terminal kinase (8).…”
mentioning
confidence: 99%
“…It also generates oxidative stress and induces the synthesis and secretion of proinflammatory cytokines and chemotaxis (9). Multiple studies have demonstrated that the AGE-RAGE interaction is involved in such disorders as diabetes (10), rheumatoid arthritis (11), and Sjögren's syndrome (12), suggesting that cellsurface binding of RAGE by AGE may be critically involved in inflammatory responses and may trigger chronic diseases. On the basis of ample published evidence, we hypothesized that RAGE might be important in mediating periapical periodontitis.…”
mentioning
confidence: 99%
“…A unique receptor of the immunoglobulin superfamily of cell surface molecules known as the receptor for advanced glycation end products (RAGE) has been implicated in chronic inflammatory conditions such as Sjögren's syndrome, diabetes, and rheumatoid arthritis [1][2][3] . RAGE signaling stimulates a host of pro-inflammatory events.…”
Section: Introductionmentioning
confidence: 99%